The effect of surrounding conditions on pixel value of cone beam computed tomography. Issue 8 (17th November 2011) - Araki, Kazuyuki; Okano, Tomohiro
Abstract: Objective: The purpose of this study was to evaluate the reliability of pixel value in CBCT, especially with regard to the effect of surrounding objects that are presented outside the field of view (FOV). Materials and methods: This experiment used the GE Hi‐Speed QXi, a multidetector helical computed tomography (MDCT) scanner, and the 3D Accuitomo FPD 8, a cone beam computed tomography (CBCT) scanner. Two types of phantoms were used, both of which contained Lipiodol Ultra Fluid (Lipiodol UF). The type A phantom was a target phantom for pixel value measurement while type B was used for the surrounding environment. For CBCT, the type A phantom was placed in a water bath, and 4 types of surrounding environmental conditions were created: (1) no other phantom present, (2) phantom type B also within the FOV, (3) half of phantom type B within the FOV, (4) phantom type B entirely outside the FOV but within the path of x‐rays aimed at phantom A. Results: In MDCT, pixel value (CT number) showed an almost linear correlation with the concentration of Lipiodol UF. In CBCT, on the other hand, pixel value was not linearly correlated with Lipiodol UF concentration. The position of the type B phantom affected pixel values in images of the type A phantom. Conclusions: Pixel value in CBCT may be affected by various conditions such as beam hardening and surrounding materials, and is therefore not reliable. Caution is essential when pixel values in CBCT are used to estimate bone density at potential implant sites.